2012
DOI: 10.2139/ssrn.2068955
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Returns and Weather Anomaly: Evidence from an Emerging Economy

Abstract: Financial economists believe that the arbitrage forces in the market are the main reason of market efficiency and these forces are the fundamental concept of efficient market hypothesis (EMH). During last few years, various theoretical and empirical evidences have been presented to support the work of financial modeling for the markets with less than rational investors whose trading strategies are based on psychological factors like mood and emotions. Weather condition is among the substantial factors affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
(1 reference statement)
1
6
0
Order By: Relevance
“…Similar findings later strengthen the theory in the study of Pilcher et al (2002). Hence, like earlier studies (i.e., Mirza et al 2012), we used the daily average temperature data as a proxy to analyse the temperature anomaly and its impact on daily stock returns in the capital markets of Pakistan and India.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Similar findings later strengthen the theory in the study of Pilcher et al (2002). Hence, like earlier studies (i.e., Mirza et al 2012), we used the daily average temperature data as a proxy to analyse the temperature anomaly and its impact on daily stock returns in the capital markets of Pakistan and India.…”
Section: Introductionsupporting
confidence: 83%
“…Extreme high temperature can result in either higher or lower returns since aggression and apathy are expected psychological outcomes but the net effect on investor risk taking depends on the tradeoff between the two. Floros (2008) and Mirza et al (2012) also found a significant negative relationship between temperature and stock returns. Although, the impact is unobservable in the daily routine, but estimated results based on sophisticated time series analysis shows a statistically significant temperature impact on stock returns for Pakistani capital market.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…However, they use one model for all the markets assuming the generalized error distribution (GED) which may not be the case for every market. Mirza et al (2012) investigate the two Pakistani markets and find that temperature is negatively related to index returns. However, they used raw temperature data only.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This gives investors an idea on how to trade in Taiwan stock market (Chang et al, 2006). Mirza et al similar study on two Pakistani stock markets, which illustration a adverse linkage amongst returns and temperature (Mirza et al, 2012). Wang (2011) concluded that knowledge, experience, and income are vital elements that sway younger generations' investing behaviors in mutual funds (Wang, 2011).…”
Section: Efficient Market Theorymentioning
confidence: 99%